Optimization of MIG welding process parameters on mechanical properties of A1-MS-SS materials - Nik Nur Fatihah Che Hassan (School of Manufacturing , University Malaysia Perlis, 2013)
The Metal Inert Gas welding is used to joint two plates of Aluminum, Mild Steel and Stainless Steel in butt joint type based on the selected parameters. The specimens used are 3mm thickness. Analysis of tensile strength using Ultimate Tensile Machine and hardness (Vickers Hardness Test) has been carried out on the surface of welding area. The highest values of tensile strength and hardness test were recorded. Taguchi method is used for design of experiment in order to obtain the optimum value for each analysis tested